Peace education from the grassroots - Harris, Ian M., 1943- (Peace education., 2013)
Historians often ignore the day-to-day struggles of ordinary people to improve their lives. They tend to focus on the accomplishments of illustrious leaders. Peace Education from the Grassroots tells the stories of concerned citizens, teachers, and grassroots peace activists who have struggled to counteract high levels of violence by teaching about the sources for violence and strategies for peace. The stories told here come from the grass roots meaning the educators are close to the forms of violence they are addressing.This collection of essays tells how citizens at the grassroots level developed peace education initiatives in thirteen different nations (Belgium, Canada, El Salvador, Germany, India, Jamaica, Japan, Mexico, the Philippines, South Korea, Spain, Uganda, and the United States). A fourteenth article describes the efforts of the International Red Cross to implement a human rights curriculum to teachers on the ground in the Balkans, Iran, Senegal, and the United Sates. These chapters describe a variety of schools, colleges, peace movement organizations, community-based organizations, and international nongovernmental organizations engaged in peace education.